Kompetensi Pengadilan Negeri Dalam Putusan Penundaan Pemilihan Umum - Aprilia, Fita; Tjiptabudy, Jantje; Nirahua, Garciano (Faculty of Law, Universitas Pattimura, 2025)
General elections are a form of implementation of democratic values, If there is an abuse of authority by the organizers of the general election, the judge has a very important role through the means of the court has the competence to resolve the election disputes that occur, The competence of the court in handling cases consists of relative competence and absolute competence. Court competence is given so that judges are not arbitrary in carrying out their duties. In reality, courts often adjudicate cases that are not their authority. Therefore, there are two problem formulations in this study, namely whether the district court has the authority to decide on the postponement of elections and what are the legal consequences of the district court's decision regarding the postponement of elections?The purpose of this study is to analyze the legal basis of the district court’s authority in deciding the postponement of general elections and to examine the legal consequences arising from such decision concerning the exercise of citizens’ constitutional rights and the duties of the election management body.Metode of research used is normative juridical, which primary legal sources and secondary sources as well as tertiary legal sources. Legislation approach, conceptual approach and case approach of the Central Jakarta District Court Decision Number 757/Pdt.G/2022/PN Jkt.Pst, which are used to solve the legal issues studied.The results of this study indicate that the Central Jakarta District Court Number: 757/Pdt.G/2022/PN.Jkt.Pst. The decision to postpone the election by the Central Jakarta Court, with a lawsuit against the government filed by the Prima Party as the plaintiff against the KPU as the defendant, is ultra vires. Ultra vires means that the decision is beyond the authority, or exceeds the authority of the judge, this is based on Law Number 30 of 2014 concerning Administration and is clarified by Supreme Court Regulation Number 2 of 2019 concerning Guidelines for Resolving Government Action Disputes and the Authority to Adjudicate Unlawful Acts by Government Agencies and / or Officials that the State Administrative Court has the authority to adjudicate disputes over unlawful acts by the government called (Onrechtmatige Overheidsdaad). The decision to postpone the general election by the district court is null and void. In order to protect the constitutional rights and the rights of citizens to conduct elections, the KPU made legal efforts to the DKI Jakarta High Court. The decision of the DKI Jakarta High Court No. 230/PDT/2023/PT then canceled the Decision of the Central Jakarta District Court No. 757/Pdt.G/2022/PN Jkt.Pst.